EVALUASI PENERAPAN BALANCED SCORECARD PADA RUMAH SAKIT UMUM DAERAH Dr. SAIFUL ANWAR MALANG - Sherlita Nurosidah; Bambang Purnomosidhi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The purposes of this research were to know the compliance of balanced scorecard implementation in RSSA Malang with the standard from Griffith et., al., (2002), to know the supporting and inhibiting factors of balanced scorecard implementation in RSSA Malang, and to describe the recommendations for balanced scorecard implementation’s problems. Balanced scorecard implementation in RSSA Malang as of 9 indicators used, 5 of them were in compliance with the standard from Griffith et., al., (2002). Indicators which in compliance with the standard were asset turnover, mortality index, occupancy, change in occupancy, and outpatient activity, in adverse 4 indicators which were not in compliance with the standard from Griffith et., al. (2002) were cash flow margin, complications index, cost per case, and length of stay. Keywords: Evaluation, Balanced Scorecard, implementation, RSSA Malang.